Financial Management, Organizational Commitment and Legislative Role on the Implementation of Good Governance at Village Governments - Yesi Mutia Basri; Leidia zurni Arfendi; Nur Azlina (The Indonesian Journal of Accounting Research, 2021)
This study aims to analyze the effect of village financial management, organizational commitment, and the role of legislative on the implementation of good governance in village governance in Siak Regency. The population in this study was the village government in Siak Regency, amounting to 122 villages, with respondents consisting of the village head, village secretary, head of finance, and village heads and village representative councils. The sampling technique in this study was proportional stratified random sampling, with a total sample of 27 village governments, with a total of 108 respondents. The data analysis method in this study is multiple regression analysis with the Statistical Package for Social Science (SPSS) v.25 program. The results of this study indicate that village financial management, organizational commitment and the role of the legislative have a positive and significant effect on the implementation of good governance. The results of this study provide input to village governments, especially to take strategic steps in order to improve governance in their villages so that good governance can be achieved.